2018
DOI: 10.1080/03019233.2018.1527538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MgO addition on the metallurgical properties of the vanadium-titanium pellet with simulating blast furnace conditions

Abstract: MgO addition plays a vital role in improving the quality of pellets. In this study, the effects of MgO addition on the compressive strength, reducibility, reduction swelling characteristics and softeningmelting performance of V-Ti pellets were explored systematically with simulating BF conditions. From the results, it can be observed that the compressive strength decreased with increasing MgO due to the formation of magnesioferrite, the restriction of recrystallization-agglomeration of haematite and the decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It could be deduced that the lattice volume swelling during the transition of magnesio-ferrite to magnesio-wustite was smaller than that of Fe 2 O 3 to FeO. 13) The increase in basicity in high MgO fluxed pellets promoted the fluidity of Mg 2 + , which might be one of the reasons for reducing reduction swelling. Meanwhile, based on the above experimental results, pellets with basicity of 0.6 to 1.3 were reduced under 1 173 K and 70% (volume percent) CO atmosphere.…”
Section: Effect Of Basicity On Rdi and Rsimentioning
confidence: 95%
“…It could be deduced that the lattice volume swelling during the transition of magnesio-ferrite to magnesio-wustite was smaller than that of Fe 2 O 3 to FeO. 13) The increase in basicity in high MgO fluxed pellets promoted the fluidity of Mg 2 + , which might be one of the reasons for reducing reduction swelling. Meanwhile, based on the above experimental results, pellets with basicity of 0.6 to 1.3 were reduced under 1 173 K and 70% (volume percent) CO atmosphere.…”
Section: Effect Of Basicity On Rdi and Rsimentioning
confidence: 95%
“…What both sinter and pellet have in common is that with the increase in MgO content, the temperature required to produce the same amount of liquid phase increases. It is well known that the premature formation of the liquid phase in the cohesive zone will result in a decrease in the permeability of the burden column and an increase in the differential pressure [22]. Therefore, the improving tendency of the gas permeability of V-Ti burden and pellet could be ascribed to the formation of material with a high melting point.…”
Section: Softening-melting Behaviormentioning
confidence: 99%
“…Large amounts preceding works demonstrated that adding MgO in pellet or sinter could enhance its high temperature properties. Zhao [22] observed that the softening-melting behavior and permeability of V-Ti pellets packed bed were improved with increasing MgO content. Umadevi T [23] studied the effect of MgO on reducibility and softening-melting behaviors of sinters.…”
Section: Introductionmentioning
confidence: 99%
“…The current research was mainly focused on the oxidation induration mechanism of aluminium-containing, silicon-containing, and titanium-containing pellets [13][14][15][16][17][18][19][20]. Wang et al [5] studied the roasting characteristics of fluorinebearing magnetite.…”
Section: Introductionmentioning
confidence: 99%